2005
DOI: 10.1097/01.ccm.0000163398.79679.66
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α-induced caspase activation mediates endotoxin-related cardiac dysfunction*

Abstract: Endotoxin induces a TNF-alpha-dependent apoptotic cascade in the myocardium, which contributes to the development of cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 64 publications
5
70
0
Order By: Relevance
“…It should be emphasized that proteases function in IB␣ degradation, as previously established (6). Calpain inhibitor III and PD-150606 are relatively specific inhibitors of calpain.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that proteases function in IB␣ degradation, as previously established (6). Calpain inhibitor III and PD-150606 are relatively specific inhibitors of calpain.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that GP administration significantly blunted NF-B activation both in septic mice (43) and in ischemic hearts (28). NF-B is a critical transcription factor in TLR-mediated signaling pathways and plays a critical role in regulation of the expression of a number of genes, including inflammatory cytokines such as TNF-␣ and IL-1-␤, which have been shown to suppress cardiac function synergistically during sepsis (10). Unfortunately, anti-TNF-␣ or anti-IL-1-␤ therapy did not result in increased survival in patients with septic shock (12).…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al examined TNF-α-dependent apoptotic pathways in isolated mouse cardiomyocytes that worked via activation of specific proteases termed capsases [37]. They found LPS injection increased capsase-3 activity in cardiomyocytes, in association with pro-apoptotic patterns of gene expression and depressed left ventricular developed pressure in ex vivo hearts.…”
Section: Other Cytokine Effectsmentioning
confidence: 99%